CHOOSING TOOLS FOR IMPLEMENTING TEXT RECOGNITION SOFTWARE - Siddikov Murodali Yuldoshaliyevich, Tokhirova Sarvinoz Gayratjon Kizi (Miasto Przyszłości, 2024)
The topic involves the process of selecting and identifying the best tools, libraries, technologies, and methods to use in creating software capable of recognizing and analyzing textual data.